2004
DOI: 10.1038/sj.bmt.1704432
|View full text |Cite
|
Sign up to set email alerts
|

Autologous hematopoietic stem cell transplantation for refractory antiphospholipid syndrome causing myocardial necrosis

Abstract: Summary:Autologous hematopoietic stem cell transplantation (HSCT) is currently being evaluated as a treatment for autoimmune diseases, including systemic lupus erythematosus (SLE), that are associated with a very severe prognosis. We describe a 27-year-old woman with SLE with a 10-year history of refractory antiphospholipid syndrome (APS). She developed progressive myocardial necrosis despite treatment with corticosteroids, cyclophosphamide (CYC), cyclosporine, and immunopheresis. After conditioning with CYC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…One of the patients with refractory disease (patient 10) died of septic shock after receiving a conditioning regimen for autologous hematopoietic stem cell transplantation (HSCT) attempted at another institution. Most published data on HSCT in APS are derived from subsets of patients with SLE (). In an open‐label trial of 22 patients with SLE and APS, 18 patients receiving long‐term anticoagulation therapy prior to autologous HSCT were able to discontinue long‐term anticoagulation therapy, with 78% of the patients remaining free of thrombosis at a median followup of 15 months ().…”
Section: Discussionmentioning
confidence: 99%
“…One of the patients with refractory disease (patient 10) died of septic shock after receiving a conditioning regimen for autologous hematopoietic stem cell transplantation (HSCT) attempted at another institution. Most published data on HSCT in APS are derived from subsets of patients with SLE (). In an open‐label trial of 22 patients with SLE and APS, 18 patients receiving long‐term anticoagulation therapy prior to autologous HSCT were able to discontinue long‐term anticoagulation therapy, with 78% of the patients remaining free of thrombosis at a median followup of 15 months ().…”
Section: Discussionmentioning
confidence: 99%
“…The study selection process is reported in Figure 1. The use of allogenic/auto-HCT as rescue therapy for SLE/SAPS was assessed using data from 2 prospective [15,36], 10 retrospective studies [16][17][18][19][20][21][22][23]34]and 13 case reports [24][25][26][27][28][29][30][31][32][33]35,[37][38][39], for a total of 279 SLE patients. Of those, 54 patients also fulfilled the criteria of APS.…”
Section: Search Results and Characteristics Of Included Studiesmentioning
confidence: 99%
“…Most reported studies described SCT for APS secondary to SLE. 23 Figure 1 The level of antiphospholipid Abs before and after treatment.…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%